Kewenangan Pejabat Pembuat Akta Tanah (PPAT) Dalam Pemungutan Bea Perolehan Hak Atas Tanah Dan Bangunan (BPHTB) Terkait Penggelapannya Dalam Akta Jual Beli - Annisa Putri Ambarwati; Rielly Lontoh Lontoh; Khalimi Khalimi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
A Land Deed Officials (PPAT) is a public official authorized to draw up authentic deeds regarding specific legal acts related to land rights. PPAT is closely associated with the collection of the Acquisition Duty of Right on Land and Building (BPHTB). In practice, the implementation of BPHTB collection often encounters challenges. One of the issues that arise is the occurrence of violations committed by PPAT in relation to BPHTB collection. The research problem in this thesis is formulated as follows: (1) What are the legal consequences for a PPAT who commits embezzlement in connection with BPHTB collection? And (2) How is the authority of PPAT in BPHTB collection regulated in relation to embezzlement in the context of a sale and purchase deed? The theoretical framework employed in this study consists of the theory of authority as developed by S.F. Marbun and Budiardjo, and the theory of legal consequences as articulated by Soeroso. The research adopts a normative juridical method, namely legal research based on literature or secondary data, utilizing primary, secondary, and tertiary legal materials. The approaches applied include the statutory approach, case approach, analytical approach, and conceptual approach. Legal materials were gathered by identifying and inventorying positive legal rules, books, journals, and other relevant legal sources. The analysis was conducted through grammatical and systematic legal interpretation, as well as legal construction methods of analogy and argumentum a contrario. The findings indicate that the legal consequences for a PPAT who engages in embezzlement related to BPHTB collection include both criminal sanctions and administrative sanctions. Furthermore, the regulation of PPAT’s authority in BPHTB collection allows the PPAT to be appointed by the Minister to act as a tax collector under the withholding system. Based on these findings, it is recommended that PPAT’s authority as a tax collector be balanced by the implementation of a user-friendly online BPHTB self-payment system for taxpayers, in order to minimize instances of embezzlement. Additionally, there should be multiple layers of oversight by the National Land Agency (BPN)/Land Office and the Regional Revenue Agency (Bapenda) to ensure the integrity and competence of PPATs